Efeito de diferentes níveis de irrigação na produtividade e ocorrência de requeima na cultura da batata - Grimm, Edenir Luis (2007)
Potato is grown in Central Rio Grande do Sul State mainly by small farmers, which use weekly sprayings with fungicides, without taking into account if meteorological conditions favor or not Late Blight and other pathogens. Water deficit can affect potato development and growth, which may affect tuber yield and quality. Irrigation applied inadequality may favor diseases due to leaf wetning. Both leaf wetning high an relative humidity play an important role in epidemic events, favoring Late Blight (Phytophthota infestans), a pathogen with high potential of causing disease. The objective of this study was to determine the effect of different levels of irrigation on yield and occurrence of Late Blight in potato cv. Asterix in the area of influence of the Meteorological Station of Santa Maria. Two experiments were conducted at the experimental field, Crop science Department, Federal University of Santa Maria. One experiment was during spring, from 21/11/2005 (emergence) to 21/02/2006 (harvest). The second experiment was during fall, from 10/04 (emergence) to 13/07/2006. The experimental design was a complete randomized, with four replications. Each replication was a 5 m x 3,2 m plot with four rows. Plant spacing was 0,8 m x 0,3 m. Fungicides used to control Late Blight were mancozebe (Dithane NT 3,0 Kg ha-1), copper oxychloride (Cuprogarb 350 4 g l-1), pyraclostrobin + metiram (Cabrio Top 3,0 Kg ha-1). The Blitecast model was used to indicate the timing of spraying, by accumulating severity values (VS) of 0 (control), 18, 24, and 30. Sprinkling irrigation was used assuming 1,0 ETm, 0,75 ETm, 0,50 ETm and no irrigation. Results showed that in dry and high temperature periods, yield was affected by irrigation, mainly when crop water demand was plenty recharged with 100% ETm. During wet periods, yield was affected by the efficient of Late Blight control. The Blitecast model with a severity value of 18 (Bli18) was the most efficient for controlling Late Blight, compared to Bli24 and Bli30, as a tool for managing fungicides application. Irrigations applied at least every there days did not affect Late Blight incidure and development